Emprego formal e a eficiência do gasto do governo : um estudo em painés dinâmicos - Almeida, Daniela Serrante de (2012)
The objective of this study is to explain the level of formal employment in the Brazilian states and the causes of its variations, assessing the level of formal employment is due solely to self-employment, product and wage or efficiency of public spending influences this dynamic. This analysis will be made considering the Brazilian states in the period 1997 to 2005. The concept of efficiency of public spending used is differentiated, taking the assumption that given the priorities of effective public administration, a large percentage of the income spent on expenditure with personnel and charges can make government inefficient. The econometric method used to estimate was dynamic panel data. The coefficients of the variables were: formal employment equal to 0,866, efficiency of government spending 0,0435, average wage -0.189 and GDP 0,0652. The long-run elasticity of the wage-employment was 1.41, 0,49 of GDP-employment and efficiency-employment 0.33, these results confirm the concept of adjustment costs of employment, making the adjustment of employment slow and distributed over the time. It has been estimated the adjustment in terms of year equal to 4.82 years. The concept of efficiency used proved to be significant in relation to employment generation, but its impact is moderate in the short and long term due to elasticity is inelastic. The study results show that efficiency of government spending in fact creates more formal employment.